Multiplatform instantaneous GNSS ambiguity resolution for triple- and quadruple-antenna configurations with constraints - Buist, P.; Teunissen, Peter; Giorgi, G.; Verhagen, S. (Hindawi Publishing Corporation, 2009)
Traditionally the relative positioning and attitude determination problem are treated as independent. In this contribution we will investigate the possibilities of using multiantenna (i.e., triple and quadruple) data, not only for attitude determination but also for relative positioning. The methods developed are rigorous and have the additional advantage that they improve ambiguity resolution on the unconstrained baseline(s) and the overall success rate of ambiguity resolution between a number of antennas.